A business ecosystem framework for SME development through associative and non-associative business structures in the digital age - Amalia Georgescu; Marc K Peter; Silvia Avasilcai (Cogent Business & Management, 2022)
Associative business structures (business associations) and non-associative business structures (those without any formal or juridical associative agreement) provide platforms to share knowledge, gain insights and collaborate. One additional benefit to participate in these structures is the opportunity for business development. In some cases, and especially for SMEs, they provide important market opportunities and access to relevant stakeholders. This literature review is aimed at identifying the concepts about associative and non-associative business structures in the context of the digital age and digital transformation. The most often referenced concepts (business networks/business relationships, the diversity of actors in a network/business ecosystems, innovative networks, and stakeholder networks/business associations) and not yet prominent concepts (digital associations/digital networks, digital ecosystems/digital environment and digital entrepreneurship, e-markets/e-business environment and e-clusters/e-hubs/digital innovation hubs) provide input and ideas of how associative business structures could be supportive and relevant for SME business development in the digital era. As a navigation aid and for future research, these concepts were summarized in a business ecosystem framework (BEF) for the digital age.
Keywords: 650; associative business structures; business development; business ecosystem; digital business; non-associative business structures; SME